ATP8B1 gene expression is driven by a housekeeping-like promoter independent of bile acids and farnesoid X receptor. - Dita Cebecauerová; Sandra S Strautnieks; Jane A Byrne; Milan Jirsa; Richard J Thompson (PLoS ONE, 2012)
BACKGROUND: Mutations in ATP8B1 gene were identified as a cause of low γ-glutamyltranspeptidase cholestasis with variable phenotype, ranging from Progressive Familial Intrahepatic Cholestasis to Benign Recurrent Intrahepatic Cholestasis. However, only the coding region of ATP8B1 has been described. The aim of this research was to explore the regulatory regions, promoter and 5'untranslated region, of the ATP8B1 gene. METHODOLOGY/PRINCIPAL FINDINGS: 5'Rapid Amplification of cDNA Ends using human liver and intestinal tissue was performed to identify the presence of 5' untranslated exons. Expression levels of ATP8B1 transcripts were determined by quantitative reverse-transcription PCR and compared with the non-variable part of ATP8B1. Three putative promoters were examined in vitro using a reporter gene assay and the main promoter was stimulated with chenodeoxycholic acid. Four novel untranslated exons located up to 71 kb upstream of the previously published exon 1 and twelve different splicing variants were found both in the liver and the intestine. Multiple transcription start sites were identified within exon -3 and the proximal promoter upstream of this transcription start site cluster was proven to be an essential regulatory element responsible for 70% of total ATP8B1 transcriptional activity. In vitro analysis demonstrated that the main promoter drives constitutive ATP8B1 gene expression independent of bile acids. CONCLUSIONS/SIGNIFICANCE: The structure of the ATP8B1 gene is complex and the previously published transcription start site is not significant. The basal expression of ATP8B1 is driven by a housekeeping-like promoter located 71 kb upstream of the first protein coding exon.